Tympanum, HSBC Building - Ghosh, Ayan (2023)
The HSBC Building was built in 1913 in a Neo-Classical style by the architectural firm Chambers & Fritchley. In 2007 and 2017, the building was carefully restored by Abha Narain Lambh Associates. The project involved the careful restoration of its basalt and limestone facades, night illumination, and restoration of its historic staircase, among other changes.